Hubungan pengetahuan ibu tentang pemberian makanan pada baduta 6-24 bulan dan status pekerjaan dengan kejadian stunting - Fahria Kum; Sunarto Kadir; Vidya Avianti Hadju (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Stunting is a chronic nutritional problem in toddlers characterized by shorter height compared to children of the same age. The formulation of the problem is whether there is a relationship between mother's knowledge about feeding 6-24 months old children and employment status with the incidence of stunting in Limba B Village, Kota Selatan District. Purpose: To determine the relationship between mother's knowledge about feeding 6-24 months old children and employment status with the incidence of stunting in Limba B urban village, South Kota sub-district. Method: This study used quantitative methods using Cross Sectional research design. The sample in this study amounted to 100 respondents, namely mothers who have 6-24 month olds. The sampling technique in the study was purposive sampling. Data were analyzed using the Chi-Square test Results: The results showed that there was a relationship between maternal knowledge about feeding 6-24 months old children with the incidence in Limba B Village with a p-value = 0.018 <0.05. And there is no relationship between maternal employment status and the incidence of stunting in 6-24 month olds with a p-value = 0.092 > 0.05. Conclusion: There is a relationship between maternal knowledge and the incidence of stunting in Limba B Village with a p-value = 0.018 <0.05. There is no relationship between maternal employment status and the incidence of stunting in toddlers in Limba B Village with a p-value = 0.092 > 0.05.